Association between fear of COVID-19 and adherence to antiretroviral treatment in people with HIV-AIDS - Vargas-Herrera, Natalia (2023)
Introduction. One of the most frequent psychological consequences of COVID-19 is fear, which could lead to non-optimal therapeutic adherence and, therefore, to the disease progression. Objectives. To evaluate the possible association between the fear of contracting COVID-19 and adherence to antiretroviral therapy in persons with HIV during the period between the third and fourth epidemic wave of COVID-19 in Peru. Methods. Analytical cross-sectional study in adults with HIV from the specialized center “Vía Libre” enrolled by non-probabilistic sampling. The validated “Fear of COVID-19 Scale” was used to measure the fear of getting sick from COVID-19, and the “SMAQ” questionnaire to assess therapeutic adherence. Results were presented descriptively, using chi-square for bivariate analysis and generalized linear models, Poisson family to calculate crude and adjusted prevalence ratios (aPR). Results. Between February and July of 2022, 149 adults with a median age of 35 years were enrolled, 91.3% being male, and 75,2% had undetectable viral load levels. No association was found between fear of contracting COVID-19 and HAART adherence (aPR: 0,99; 95% CI 0,97 to 1,02). Persons with a comorbidity were 89% more adherent than persons without comorbidities (RPa: 1,89; 95% CI 1,52 to 2,35). Conclusion. The fear of contracting COVID-19 was not associated with adherence to HAART during the third wave of COVID-19 pandemic in Peru. However, presenting a comorbidity was associated with optimal HAART adherence. Emphasis should be placed on potential factors affecting medication adherence in people with HIV during the COVID-19 pandemic.